The Impact of Dietary Fucosylated Oligosaccharides and Glycoproteins of Human Milk on Infant Well-Being - Orczyk-Pawiłowicz, Magdalena (Nutrients, 2020)
Apart from optimal nutritional value, human milk is the feeding strategy to support the immature immunological system of developing newborns and infants. The most beneficial dietary carbohydrate components of breast milk are human milk oligosaccharides (HMOs) and glycoproteins (HMGs), involved in both specific and nonspecific immunity. Fucosylated oligosaccharides represent the largest fraction of human milk oligosaccharides, with the simplest and the most abundant being 2′-fucosyllactose (2′-FL). Fucosylated oligosaccharides, as well as glycans of glycoproteins, as beneficial dietary sugars, elicit anti-adhesive properties against fucose-dependent pathogens, and on the other hand are crucial for growth and metabolism of beneficial bacteria, and in this aspect participate in shaping a healthy microbiome. Well-documented secretor status related differences in the fucosylation profile of HMOs and HMGs may play a key but underestimated role in assessment of susceptibility to fucose-dependent pathogen infections, with a potential impact on applied clinical procedures. Nevertheless, due to genetic factors, about 20% of mothers do not provide their infants with beneficial dietary carbohydrates such as 2′-FL and other α1,2-fucosylated oligosaccharides and glycans of glycoproteins, despite breastfeeding them. The lack of such structures may have important implications for a wide range of aspects of infant well-being and healthcare. In light of the above, some artificial mixtures used in infant nutrition are supplemented with 2′-FL to more closely approximate the unique composition of maternal milk, including dietary-derived fucosylated oligosaccharides and glycoproteins.